AN ANALYSIS OF AN ENGLISH TEXTBOOK ENTITLED “FORWARD AN ENGLISH” PUBLISHED BY ERLANGGA FOR TWELFTH GRADE VOCATIONAL SCHOOL STUDENTS - Diah Puspita Ayu; Susan Ira Nova; Lesly Martha Cecylia Meka; Sulamit Syeba (PROJECT (Professional Journal of English Education), 2024)
This research presents a thorough examination of the English course book titled "Forward an English" by Erlangga, for Twelfth Grade Vocational School Students. The primary objective of the study was to assess the course book's content feasibility and presentation in accordance with the Education National Standard Council (BSNP) guidelines. The methodology applied in this research was content analysis. The findings of this research indicate that "Forward an English" by Erlangga, for Twelfth Grade Vocational School Students course book largely fulfills 67.90% of the BSNP criteria for standard course books in terms of content feasibility. Concerning the presentation feasibility, the coursebook adequately addresses approximately 66.67% of the relevant categories. Therefore, based on the evaluation following BSNP's rubric assessment, it can be deduced that the book serves as a SUFFICIENT resource.